2015
DOI: 10.2498/cit.1002535
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing User�s Attitude to Secondary Information Sharing and Usage

Abstract: The increasing availability of enormous data about users online, along with availability of sophisticated tools and technology to store, aggregate, and analyze data for secondary use has raised concerns about how to balance the opportunity for secondary use of data with the need to protect the user privacy that may result from harmful use. To develop a privacy protection mechanism that is useful and meets the expectations and needs of the user, it is important to understand user's attitude to privacy and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Individuals with high subjective knowledge are often opinion leaders; their experience or specialized knowledge positively impacts their knowledge-sharing intention [30]. Iyilade et al [55] found that as personal perceived risk increases, the likelihood of promoting knowledge sharing decreases. When people perceive high risks in using online communities, they may be unwilling to use them and feel concerned about the information shared in these communities.…”
Section: Willingness Of Knowledge Sharingmentioning
confidence: 99%
“…Individuals with high subjective knowledge are often opinion leaders; their experience or specialized knowledge positively impacts their knowledge-sharing intention [30]. Iyilade et al [55] found that as personal perceived risk increases, the likelihood of promoting knowledge sharing decreases. When people perceive high risks in using online communities, they may be unwilling to use them and feel concerned about the information shared in these communities.…”
Section: Willingness Of Knowledge Sharingmentioning
confidence: 99%
“…However, studies of attitudes toward inferred information from disclosed user data remain scant. While a small number of studies on secondary use exist (Adjei & Olesen, 2012;Boateng & Okoe, 2015;Iyilade, Orji, & Vassileva, 2015;Soczka, Brites, & Matos, 2015), they are focused on SNSs' practices of handling personal information.…”
Section: Privacy Awareness and Attitudes Toward Inferences Made Usingmentioning
confidence: 99%